Spatio-specific regulation of endocrine-responsive gene transcription by periovulatory endocrine profiles in the bovine reproductive tract - Araujo, Estela R.; Sponchiado, Mariana; Pugliesi, Guilherme; Van Hoeck, Veerle; Mesquita, Fernando S.; Membrive, Claudia M. B. [UNESP]; Binelli, Mario (Csiro Publishing, 2016)
In cattle, pro-oestrous oestradiol and dioestrous progesterone concentrations modulate endometrial gene expression and fertility. The aim was to compare the effects of different periovulatory endocrine profiles on the expression of progesterone receptor (PGR), oestrogen receptor 2 (ESR2), oxytocin receptor (OXTR), member C4 of aldo-keto reductase family 1 (AKR1C4), lipoprotein lipase (LPL), solute carrier family 2, member 1 (SLC2A1) and serpin peptidase inhibitor, clade A member 14 (SERPINA14): (1) between uterine horns ipsi- and contralateral to the corpus luteum (CL), (2) between regions of the ipsilateral horn and (3) in the vagina. Endometrium and vagina tissue samples were collected from cows that ovulated a larger (large follicle-large CL, LF-LCL; n=6) or smaller follicle (small follicle-small CL, SF-SCL; n=6) 7 days after oestrus. Cows in the LF-LCL group had a greater abundance of transcripts encoding ESR2, AKR1C4, LPL, SLC2A1 and SERPINA14, but a reduced expression of PGR and OXTR in the endometrium versus the SF-SCL group (P<0.05). Expression of PGR and OXTR was greater in the contralateral compared with the ipsilateral horn (P<0.05). Regardless of group, the anterior region of the ipsilateral horn had increased expression of PGR, ESR2, LPL, SLC2A1 and SERPINA14 (P<0.05). Different periovulatory endocrine profiles, i.e. LF-LCL or SF-SCL, did not influence gene expression in the vagina and had no interaction with inter- or intra-uterine horn gene expression. In conclusion, inter- and intra-uterine horn variations in gene expression indicate that the expression of specific genes in the bovine reproductive tract is location dependent. However, spatial distribution of transcripts was not influenced by distinct periovulatory sex-steroid environments.
Keywords: oestradiol; progesterone; transcript abundance; uterine horn; vagina